(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
A survey was made to the students of the Instituto Tecnológico de Tlaxiaco, Oaxaca , Mexico about the interactive platforms they use the most in their homework, in addition to this it was highlighted that some students are fluent in Spanish and other students are fluent in Spanish and an indigenous language, in this way the students were questioned about which indigenous language they speak, write or read, in order to know how they interact with interactive technologies that offer new opportunities to improve their education, facilitating an inclusive and effective learning. This work considered: the type of device they usually use, the interactive platforms they use the most for different research or laboratory projects and schoolwork. It is important to mention that facilitating access to technology for indigenous-speaking students promotes digital inclusion and offers opportunities where significant impacts are shown in their education, to overcome barriers and improve their learning conditions.